EVALUATION OF PRACTICES IN THE EDUCATION PROCESS IN THE CONTEXT OF AGENDA SETTING THEORY - Oteles, Ulku Ulukaya; Evcimen, Fatima Betul Demir; Kocoglu, Erol; Avcu, Kubra Melis (Scientia Socialis, 2024)
In today's world, where the internet-based digitalization process has gained momentum, increasing the quality of learning in the educational process can be achieved by associating the transferred achievements with current topics and news in written and visual media by the teacher of the course, thus increasing the attention level of the learners in the learning environment. This situation, which shows the impact of the agenda on the educational process, increases the awareness level of the learners regarding the time period in which they live, the environment and the events that occur. In this direction, this study aimed to identify and evaluate the practices in the education process in the context of agenda setting, in line with teachers' opinions. This study, which was carried out with the phenomenology pattern, one of the qualitative research methods, was conducted with 30 teachers working in public schools. The data of the research were collected with a semi-structured interview form. The data obtained was analyzed with content analysis. As a result of the study, it was determined that the practical reflections of the activities prepared by the teachers based on the agenda setting theory were not sufficient in the context of learning.
Keywords: Agenda setting; educational practice; phenomenological design